Financial Management Practices Among Micro-Scale Business Owners in Purbalingga - Fitriana, Aning; Wirawan, Nugroho Budi (International Journal Business and Entrepreneurship, 2025)
This research aims to analyze financial management practices among micro business actors (UMKM) in the coffee sector in Purbalingga Regency. A qualitative approach was used through interviews with 10 coffee-based UMKM owners as key respondents. The findings suggest that monetary governance exerts a considerable influence on corporate. sustainability. Three main indicators were analyzed: financial planning, financial implementation, and financial control. Financial planning which includes managing production, sales, savings, investments, cash reserves, and separating personal and business finances is categorized as good and directly contributes to increased business income. However, financial implementation and control, particularly in aspects of financial recording, reporting, and supervision, are not yet optimal. This is largely due to the limited knowledge and financial management skills of most business owners, as well as the perception that such practices are unnecessary for small scale businesses. This study recommends that future research adopt a quantitative approach with a larger respondent base and explore internal and external factors influencing financial management. Furthermore, the development of practical interventions such as technology based training and simple financial recording applications is also suggested to enhance financial management capabilities among UMKM entrepreneurs.